Viet Nam in 3D : Using Geospatial Technology to Better Understand Military History - Schleicher, Brandon (My University, 2012)
Many Viet Nam conflict historians have struggled with describing the tortuous relief of the Viet Nam landscape. Traditional hard copy maps, lacking a three-dimensional perspective, along with mere textual descriptions, are often inadequate in describing how terrain was one of many difficulties soldiers faced during the Viet Nam conflict. Advancements in computer mapping technology have provided a valuable set of tools for visualizing historic information. This study focuses on the Khe Sanh battlefield, and how the relief and its hilltops were key factors in the battles that occurred there in 1967 and 1968.
Color poster with text images, maps, and photographs.
Keywords: Vietnam--Historical geography; Three-dimensional imaging; Geospatial data; Vietnam--History, Military; Posters